Gendering the transnational : Gender und Medien transnationaler Historiografie im Musée des civilisations de l’Europe et de la Méditerranée Marseille (MuCEM) - Czerney, Sarah (My University, 2015)
The article examines how national museums currently try to overcome national narratives by focussing on the former ethnological national museum in France, the MuCEM in Marseille. Starting from the observation that ‘general’ national history is male and white, written mainly by white men and marginalizing women’s lives, this article asks whether the opening of national towards transnational museums leads to a deconstruction of hegemonic identity categories like ‘nation’ and ‘gender’. The paper therefore analyzes one selected display from the MuCEM with a focus on the media used to exhibit transnational history.
Keywords: Gender; Kunst; 700 Künste; Bildende und angewandte Kunst; Museum; Ausstellung